EFECTO DEL RENDIMIENTO DE CURSOS PREUNIVERSITARIOS EN EL RENDIMIENTO DE PRIMER AÑO DE MEDICINA - Tucto Berríos, Joel (2017)
Introduction: The present research work allowed knowing whether the performance of subjects in the pre university center Valdizano CEPREVAL is related to the performance of various subjects of the first year of university studies of the Academic Professional School of Human Medicine, in the National University Hermilio Valdizán of Huánuco. Methods: For whose purpose was considered the subjects of Mathematical aptitude, Verbal Ability, Chemistry, Biology and Anatomy of CEPREVAL as variables of the independent vector, and the subjects of Mathematics and Logical; Language and Communication, Medical Chemistry, Human Anatomy and Cell and Molecular Biology, of the first year of studies, of Academic Professional School - human medicine; as, variables of the dependent vector. These variables were analyzed in a sample of 35 medical students who entered in 2005 and 2006 by the modality of CEPREVAL. The integral analysis of the data consisted of measurement of association between the canonical variables of the dependant and independent vectors, through the application of Canonical Correlation Analysis. The type of study utilized was correlational, retrospective and longitudinal. Results:Two were the canonical correlations that were excellent for a significance level from 0.05. The first canonical correlation achieved greater average level (0.792) and the second correlation obtained the value of 0.538. The courses that contribute significantly to the performance of students in the first year of university studies were Verbal Ability, Mathematical aptitude, Mathematics and Logical; Language and Communication, Medical Chemistry and Human Anatomy. There was no significant contribution of the courses of Biology, and Cellular Molecular Biology. Conclusions: The results allowed concluding that the academic performance of first-year subjects of university study in the Academic Professional School - Human Medicine is correlated in joint form with the performance of CEPREVAL courses.